Plasma Process. Polym. 3/2013. Issue 3 (7th March 2013) - Fouquet, Thierry; Petersen, Julien; Ziarelli, Fabio; Bour, Jérôme; Toniazzo, Valérie; Ruch, David; Charles, Laurence
<x xml:space="preserve">Abstract</x> Cover: Partial ethanolysis of unsoluble silicon‐based plasma polymers into a mixture of small oligomers amenable to mass spectrometry analysis allows the architecture of the original solid network to be reconstructed. The cover images is presented by L. Charles et. al., and further details can be found on page 271. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>